DEVELOPMENT OF SOCIAL WORK AND CORE SUBJECTS OF SOCIAL WORK EDUCATION IN THREE EUROPEAN COUNTRIES - Ivaškaitė-Tamošiūnė, Viginta (Socialinė teorija, empirija, politika ir praktika, 2007)
The goal of the paper is to analyse the development of social work profession and studies in three European countries: Greece, Germany and Lithuania. The comparative method is used. The objects of the analysis are: the origin of social work and its education, foundation of fist schools, and their creators, further development of education, levels and duration of social work education, credits system, the core subjects of studies, practical work and specializations. The findings show that there is a lot of in common, as well as different in the area of social work. Commonalities of social work development were related mostly to each country's social, economical, political transformation that resulted in great changes in terms of the need of professional help and the acceptance of social work profession. Meanwhile differences mainly occurred when analysing the time of emergence of a particular stage and the rapidity of development. It was observed that commonalities in Germany, Greece and Lithuania lie mainly in core subjects of social work, importance of practical training, as well as in numerous specializations offered. Differences come about when looking at the formal system that is based on undergraduate and graduate cycles, and the credits system.
Keywords: Social work development; social work education; social work curriculum; core subjects